Development and Evaluation of Isoniazid Loaded Silk Fibroin Microsphere - Narinder Singh; Surya Prakash Gautam; Harjaskaran; Amanjot; Lovepreet Singh; Ankit Verma; Shalu Rani
Aim: Current experimental investigation is dedicated to prepare microspheres with small size and good sphericity by Phase Separation method using Isoniazid (INH) as model drug. Silk fibroin has unique intrinsic qualities like biodegradability, biocompatibility or release properties and their tunable drug loading capacity. The delivery loading proficiency of the drug molecules in silk spheres be contingent on their charge, and hydrophobicity or subsequent in altered drug release profiles. Methods: In the present work Isoniazid loaded silk fibroin microsphere was prepared by using phase separation method. Microsphere was evaluated for Ultraviolet-visible spectroscopy, Fourier Transform infrared spectroscopy, Entrapment efficiency, Scanning electron microscopy Studies. Results: Scanning electron microscopy studies revealed that Isoniazid Loaded Silk Fibroin Microspheres were spherical. Entrapment Efficiency of Isoniazid loaded Microspheres of different Formulation from F1 to F5 was in range of 53 to 68 %. F3 showed 68.47 % entrapment Efficiency and the optimized formulation drug release was 93.56 % at 24 hours. Conclusion: Experimental report disclosed a new aqueous based formulation method for silk spheres with controllable shape or size and sphere. Isoniazid loaded silk microspheres may act as ideal nano formulation with elaborated studies.